Review of Eric Porter. 2002. What Is This Thing Called Jazz?: African American Musicians as Artists, Critics, and Activists. Berkeley: University of California Press - Gabbard, Krin (Current Musicology, 2001)
For too long, jazz writers, including the handful of academics who can legitimately be called ‘Jazz scholars,” promoted myths of the music’s autonomy. According to this myth, the identity of the musicians, the venues where they performed, and what they said off the bandstand were of little or no importance. It was all about the music. This conviction led the esteemed jazz scholar Gunther Schuller to write a huge book on the Swing Era that consists almost entirely of record reviews. Writing on Louis Armstrong in The Swing Era, Schuller goes out on a limb and says that “one must eventually come to grips with the totality of his life and work. This can only be done in a dispassionate way, which also takes into account Louis’s personality and temperament, and the social-economic conditions within which he labored” (1989:160). This call, however, is in a footnote, and there is virtually nothing in Schuller’s book that follows through on his own suggestions about how to understand Armstrong’s life and work. It is also significant that Schuller omits any reference to what Armstrong, a highly prolific writer himself (see Armstrong 1999), may have had to say about those “social-economic conditions.” Many of us in the jazz studies community are now likely to agree that it’s never just about the music. The music only means what it is allowed to mean. For most of its one hundred year history, jazz has been colonized by critics, most of them white, who have imposed their own meanings on the music. And during much of this period, jazz artists, most of them African American, have struggled to combine their words with their musical utterances in order to create their own meanings.